Problematic Questions Related to Lawsuit Enforcement in the Georgian Jurisdiction System - Chanidze, Dali (European Scientific Journal, ESJ, 2017)
In the given article we will discuss lawsuit enforcement questions and methods which have acutely arisen and made contentious the problem of its necessity and its usage in jurisdiction in the recent period. Accordingly, it became necessary to research and study lawful nature of lawsuit enforcement measures as an important institute of the Public Procedural Law. In our opinion, courts have to install a unanimous practice in regard to lawsuit enforcement methods. Although, we must observe that it was not our aim to give general characteristics of the suit enforcement as an institute or to discuss its various methods. In this article we will try to characterize the criteria of the lawfulness of the lawsuit enforcement measures and also problems of its usage, abstaining from it and of its change as based on the Georgian jurisdiction and the existing law practice in Georgia .